2009
DOI: 10.1159/000268123
|View full text |Cite
|
Sign up to set email alerts
|

The Placebo Response Rate in Irritable Bowel Syndrome and Inflammatory Bowel Disease

Abstract: The placebo response is the efficacy attributable to a treatment that is thought to have no specific pharmacologic effect on the condition being treated. Although potentially helpful in clinical practice, high and unpredictable placebo response rates present a major impediment to the success of clinical trials in inflammatory bowel disease (IBD) and irritable bowel syndrome (IBS). Diverse factors contribute to the placebo response rates observed in clinical trials. These include patient characteristics, physic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 41 publications
(24 reference statements)
1
10
0
Order By: Relevance
“…Human IBD drug trials, particularly those in Crohn's disease, are complicated by both uncertainty about current disease activity and also by the relapsing and remitting clinical course. These variables are believed to be significant contributors to high placebo rates, which can obscure therapeutic benefits of drug candidates (Su et al 2004;Sands et al 2005;Sands 2009;D'Haens et al 2012). The need to reduce placebo risk in IBD trials has led to increasing use of expensive and sometimes invasive imaging modalities to compensate for the lack of highly reliable indicators of disease activity (Solem et al 2008;Loftus et al 2007;Buisson et al 2013), so development of reliable and noninvasive disease activity biomarkers is an ongoing area of interest.…”
Section: Utilization Of Animal Models In Ibd Researchmentioning
confidence: 99%
“…Human IBD drug trials, particularly those in Crohn's disease, are complicated by both uncertainty about current disease activity and also by the relapsing and remitting clinical course. These variables are believed to be significant contributors to high placebo rates, which can obscure therapeutic benefits of drug candidates (Su et al 2004;Sands et al 2005;Sands 2009;D'Haens et al 2012). The need to reduce placebo risk in IBD trials has led to increasing use of expensive and sometimes invasive imaging modalities to compensate for the lack of highly reliable indicators of disease activity (Solem et al 2008;Loftus et al 2007;Buisson et al 2013), so development of reliable and noninvasive disease activity biomarkers is an ongoing area of interest.…”
Section: Utilization Of Animal Models In Ibd Researchmentioning
confidence: 99%
“…IBS type symptoms may account for the high placebo responses sometimes seen with CDAI use in trials. (10, 11) These high placebo rates lead to difficulty in demonstrating treatment efficacy, as evidenced by a recent trial of certolizumab in CD, where the use of biomarkers as objective measures of disease activity may have enhanced the ability to reach statistical significance. (12) In UC, mucosal healing can be assessed by flexible sigmoidoscopy; however, this test is invasive and adds significant cost to care.…”
Section: Historical Measurement Tools Of Ibd Activitymentioning
confidence: 99%
“…Comparison of different definitions of success is complex, as a patient could be considered in remission by one trial but in a state of active disease by another. In addition, clinical trials of treatments of UC are known to have a diverse and unpredictable placebo response rate [206]. A 2007 meta-analysis of 40 clinical trials found that placebo induced remission rates ranged from 0-40% while placebo response was as high as 67% [207].…”
Section: Safety and Toxicology Of Probioticsmentioning
confidence: 99%
“…Shorter trials with fewer study visits lessen the cost of the study and reduce placebo values [206]. Long term trials may document a decrease in clinical effectiveness as relapses occur, the treatment ceases working and symptoms return.…”
Section: Safety and Toxicology Of Probioticsmentioning
confidence: 99%